Tingkat self-regulated learning mahasiswa melalui pembelajaran blended learning berbasis aplikasi Google Classroom - Muhammad Ilham Bakhtiar (Seminar Nasional LP2M UNM, 2019)
The research objective is to find out (1) the description of student Self Regulated Learning, and (2) the role of Blended Learning through the Google Classroom Application to improve Self Regulated Learning. This article is described through a literature review describing various reference sources and phenomena that occur in the field. The results of this study are: (1) Independent learning or Self regulated learning is applied through a combination of academic learning skills and self-control can be realized through the setting of the learning environment. The environment will be the cause of the encouragement of students to be able to learn independently without having to wait for instructions, direct instructions from the lecturer, but rather driven by their own desire to learn from the instructions used through learning media. based learning full involvement of students such as blended learning. Blended models provide many advantages, the benefits lie in their accessibility, flexibility in scheduling students, and adaptability to work independently and in groups. (2) Independent learning through blended learning as a combination of traditional and traditional learning is done through the google clsasroom application because it has various benefits in encouraging students to improve their own learning skills, namely (1) Assigmenments are useful for assignments, assignments will be stored and assessed in the google productivity application series which allows collaboration between teachers and students or students to students; (2) Grading is useful for measuring or evaluating the work performed; (3) Communication is useful for communication between lecturers and students through posts and comments; (4) Time-Cost aims for time management; (5) Archive Course is useful for archiving data and learning material documents during the running class; (6) Mobile applications are available in the form of applications on mobile phones or playstores